PENINGKATAN KUALITAS KEASAMAN (pH) PADA SUMBER AIR UNTUK INDUSTRI AIR MINERAL DENGAN METODE PENYARINGAN - Ariyani, Sukma; Asmawit; Utomo, Pramono; Cahyanto, Heru (JURNAL BORNEO AKCAYA, 2020)
Good quality water is a necessity for living things for their survival. Mineral water sources for industry raw materials include groundwater and surface water. The quality of the ground water taken from Anjongan Subdistrict, Mempawah District, West Kalimantan, which was used as a water source did not meet the acidity value requirement (pH) following the Health Ministerial Regulation No. 416 / MENKES / IX / 1990 as tested by one of mineral water companies in West Kalimantan as required by SPPT SNI . The purpose of this study was to increase the pH value of source water so that it is suitable for use as raw water. Three types of filter material, namely, quartz sand, manganese sand, and activated carbon, were used to increase the pH value. The results showed that the water that was filtered using activated carbon increased the pH value by increasing the percentage of 18.7%, increasing the pH from 5.68 to 6.74 so that it met the quality standard (pH 6.5-9); while filtering with sand manganese and quartz sand, the result of the increase in pH did not meet the standards. Local governments could offer solutions to improve the quality of raw water acidity to other companies with the same obstacles in the company. Keywords: activated carbon, filtration, pH, water